Sistem bantuan keputusan bagi kawalan pembangunan di kawasan tanah tinggi dan lereng bukit - Amiruddin, Satria Gandhini (2006)
This thesis deals with design and development of a decision support system to assist decision makers in evaluating development application for high land and hill side areas. The process of evaluating the development application requires decision makers to refer to information that are stored in multiple media and media types. This has led the decision makers to spend a lot of time searching for relevant information and to process the data, before making judgment about a development application. The Decision Support System (DSS) developed in this research contains three main components. First, the Geographic Information System (GIS) component will support decision makers in retrieving development site data in the spatial context. Since most of the criteria and reference material uses height and slope classification, the Inverse Distance Weighted (IDW) technique is used to interpolate them using the contour layer. IDW is an old technique, but this study shows that it is sufficient for the task assuming density of points in the contour layer is high. Second, a decision synthesis component uses multi-criteria analysis, specifically Analytical Hierarchical Process (AHP), to provide decision makers with the initial analysis of development site characteristic. Lastly, a guidelines recognition component, to help search for relevant guidelines that decision makers need to consider in making judgment of a development application. This component uses rule-based method to find relevant guidelines based on development site characteristics. With all three components in place, the decision makers should be able to focus most of his/her time in evaluating development application